Vitamin D and melatonin protect the cell’s viability and ameliorate the CCl4 induced cytotoxicity in HepG2 and Hep3B hepatoma cell lines - Özerkan, Dilşad; Özsoy, Nesrin; Yılmaz, Erkan (Springer Science and Business Media LLC, 2014)
Carbon tetrachloride (CCl4) is widely used to induce liver toxicity in in vitro/in vivo models. Lipid peroxidation (LPO) begins with toxicity and affects cell viability. Recently, the beneficial effects of melatonin and Vitamin D on cell proliferation in human normal and cancer cells were found. This study was planned to evaluate antioxidant and cytoprotective activity of melatonin and Vitamin D in CCl4 induced cytotoxicity in HepG2 and Hep3B hepatoma cell lines. Based on the cytotoxicity assay, melatonin and Vitamin D were evaluated for cytotoprotective potential against CCl4 induced toxicity in HepG2 and Hep3B liver cell lines by monitoring cell viability, LPO and glutathione (GSH) level. Different dosages of CCl4 (0.1, 0.2, 0.3 and 0.4 % v/v) were applied to HepG2 and Hep3B cells in order to determine the most toxic dosage of it in a time dependent manner. The same experiments were repeated with exogenously applied melatonin (MEL) and Vitamin D to groups treated with/without CCL4. Cell viability was determined with MTT measurements at the 2nd, 24th and 48th h. GSH content and Malondialdehyde levels were measured from the cell lysates. As a result, both melatonin and Vitamin D administration during CCl4 exposure protected liver cells from CCl4 induced cell damage. Increase in LPO and decrease in GSH were found in the CCl4 groups of both cells. Contrary to these results administration of MEL and Vitamin D on cells exhibited results similar to the control groups. Therefore, melatonin and Vitamin D might be a promising therapeutic agent in several toxic hepatic diseases.
Keywords: 3. Good health